2015
DOI: 10.1177/0743558415587325
|View full text |Cite
|
Sign up to set email alerts
|

“That’s Just How It Is”

Abstract: In this mixed-methods study, we adopted a feminist theoretical lens in conceptualizing gender as hierarchical and complementary ideologies—femininity and masculinity—that are fundamental constituents of institutionalized heterosexuality as a way to understand the persistence of gender inequity in adolescents’ heterosexual relationships. In Study 1, we conducted separate analyses for girls and boys to evaluate whether masculinity ideology for boys and femininity ideology for girls account for boys’ endorsement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…32-33) While developmental researchers have not considered the study of gender socialization, for example, as a study of accommodation to ideological structures, it is, in fact, the study of how boys and girls adopt dominant gender ideologies in their peer groups, identities, and school behaviors [e.g., Cvencek et al, 2011;Fabes et al, 2004;Liben, 2017;Tobin et al, 2010]. The study of boys, in addition, typically reveals how boys align with masculine norms [Chu, Porche, & Tolman, 2005;Cunningham, Swanson, & Hayes, 2013;Kimmel, 2008;Pleck, Sonenstein, & Ku, 1993;Majors & Billson, 1992;Tolman, Davis, & Bowman, 2015]. Developmental studies have also focused on accommodation to racist ideologies and revealed how children "learn" or accommodate to such ideologies in their racial attitudes and stereotypes [e.g., Slaughter-DeFoe, 2012].…”
Section: Accommodation and Resistance To Cultural Ideologiesmentioning
confidence: 99%
“…32-33) While developmental researchers have not considered the study of gender socialization, for example, as a study of accommodation to ideological structures, it is, in fact, the study of how boys and girls adopt dominant gender ideologies in their peer groups, identities, and school behaviors [e.g., Cvencek et al, 2011;Fabes et al, 2004;Liben, 2017;Tobin et al, 2010]. The study of boys, in addition, typically reveals how boys align with masculine norms [Chu, Porche, & Tolman, 2005;Cunningham, Swanson, & Hayes, 2013;Kimmel, 2008;Pleck, Sonenstein, & Ku, 1993;Majors & Billson, 1992;Tolman, Davis, & Bowman, 2015]. Developmental studies have also focused on accommodation to racist ideologies and revealed how children "learn" or accommodate to such ideologies in their racial attitudes and stereotypes [e.g., Slaughter-DeFoe, 2012].…”
Section: Accommodation and Resistance To Cultural Ideologiesmentioning
confidence: 99%
“…Feminist theories and research on gender inequities in heterosexual relationships have articulated the challenges to and importance of young women's sexual subjectivity for sexual well-being, sexual safety, and health (i.e., Bay -Cheng, 2015a;Fahs, 2011;Fine & McClelland, 2006;Horne & Zimmer-Gembeck, 2005;Tolman et al, 2016). Sexual subjectivity, which is broadly defined as a person's understanding and experience of themselves as a sexual being, has been theorized and empirically demonstrated to have several distinct dimensions: (a) one's awareness of her embodied feelings of desire, pleasure, and/or sexual responses, (b) one's sense of entitlement to those feelings, and (c) one's agency or ability to recognize and utilize bodily, relational, and cognitive information in acting in the interest of her own sexual needs (Horne & Zimmer-Gembeck, 2005;Martin, 1996;Schick et al, 2008;Tolman, 2002).…”
mentioning
confidence: 99%
“…Gender stereotypes are a combination of personality traits, attitudes, values, and behaviors that characterize the social expectations of men and women (Sánchez-Bravo et al, 2005). In general, most cultures differ in terms of the social expectations for men and women concerning behavior in sexual situations (Tolman et al, 2016). In Latin American cultures, these social expectations are quite conservative.…”
Section: Gender Stereotypesmentioning
confidence: 99%